2007
DOI: 10.1007/s11248-007-9149-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of promoter driving selectable marker on corn transformation

Abstract: Identification of an appropriate selection agent and its corresponding selectable marker gene is one of the first steps in establishing a transformation protocol for a given plant species. As the promoter controls expression level of the genes, the promoter driving the selectable marker gene can affect transformation. However, investigations into the direct effect of promoters driving selectable marker on transformation are lacking in the literature though many reports of relative strengths of promoters drivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…In some cases, transgene expression that is too strong might be disadvantageous. For example, high expression of a selectable marker gene has been reported to produce leakage of the protein that confers resistance to antibiotic to adjacent non-transformed cells, resulting in false-positive transformants (Prakash et al 2008). High expression of transgenes might be also harmful for the growth of embryogenic calli and plant regeneration, probably because of increased use of energy and resources for the expression of transgenes and its proteins (Potenza et al 2004;Zhou et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, transgene expression that is too strong might be disadvantageous. For example, high expression of a selectable marker gene has been reported to produce leakage of the protein that confers resistance to antibiotic to adjacent non-transformed cells, resulting in false-positive transformants (Prakash et al 2008). High expression of transgenes might be also harmful for the growth of embryogenic calli and plant regeneration, probably because of increased use of energy and resources for the expression of transgenes and its proteins (Potenza et al 2004;Zhou et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Particle preparation 'Cassette DNA fragment' at a rate of 1.0 or 10 or 100 ng or 'entire plasmid' at a rate of 100 ng was precipitated respectively on 1.8 mg gold particles (0.6 l diameter; BioRad, Hercules, CA) as described previously by Shiva Prakash et al 2008. Each of these DNA coated gold preparations was used for four shots (bombardments), giving an effective delivery of 0.25 or 2.5 or 25 ng of cassette DNA or 25 ng of entire plasmid DNA coated on 0.45 mg gold particles per shot.…”
Section: Constructs Used In Transformationmentioning
confidence: 99%
“…Particle delivery using the helium PDS-1000 device Bombardment was performed using the PDS-1000/He Particle Delivery System TM (Bio-Rad) as described previously (Shiva Prakash et al 2008).…”
Section: Constructs Used In Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been observed that other promoters are stronger than the 35S promoter when used for in vitro transformation of different monocot and dicot plants. Indeed, the Cauliflower Mosaic Virus (CaMV) 35S promoter was less effective in driving the GUS gene expression in tomato (dicot) and maize (monocot) plant tissues as compared to the maize promoters Gos-2, Enolase, Actin-2 (Shireen et al, 2002) and Actin-1 (Prakash et al, 2008). By using immature and mature embryos, shoot tips and embryogenic calli for in vitro transformation of S. bicolor, Tadesse et al (2003) observed that the strength of the CaMV 35S promoter ranked after those of the ubi1, act1D, adh1 promoters.…”
Section: Discussionmentioning
confidence: 99%